Kontribusi efikasi diri terhadap kinerja guru bimbingan dan konseling - Linda Kahar; Afiatin Nisa; Cindy Marisa; Sabrina Dachmiati (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the aim of this study was to find out whether self-efficacy contributes to the performance of guidance and counseling teachers. This research was carried out with a survey-type quantitative approach. The target population of this study were 60 guidance and counseling teachers at SMA and SMK Negeri Kota Kendari. This research is a population study so that the entire population of 60 people becomes the research sample. Data was collected through teacher self-efficacy and performance scales. Data were analyzed descriptively and inferentially with the results: a) the self-efficacy of guidance and counseling teachers in SMA and SMK Negeri Kota Kendari was in the moderate category, b) the performance of guidance and counseling teachers in SMA and SMK Negeri Kota Kendari was in the medium category, and c) self-efficacy contributes significantly to the performance of guidance and counseling teachers in SMA and SMK Negeri Kota Kendari.